RUANG BELAJAR BARU DAN IMPLIKASI TERHADAP PEMBELAJARAN DI ERA TATANAN BARU - Uwes Anis Chaeruman (Kwangsan: Jurnal Teknologi Pendidikan, 2020)
The Pandemic Coronavirus Disease (Covid-19) has taken place all over the world. This situation has affected all sectors of human life, likewise in the education sector. Physical distancing policy has forced all countries to close the school. Distance and online learning have become the only option to solve it. This article tried to answer two questions. First, what are the essences of learning spaces in the context of e-learning viewed from the perspective of time and space synchronicity? Second, what are the implications of it to the implementation of teaching and learning in the era Covid-19 and new normal? The researcher applied literature review to answer those questions. Literatures review result showed that learning space can be divided into four categories. This classification provides some implications toward the implementation of teaching and learning in the era of Covid-19 and new normal. AbstrakPandemi virus corona (Covid-19) telah melanda seluruh dunia. Bencana kejadian luar biasa ini telah berpengaruh terhadap semua sektor kehidupan manusia, termasuk sektor pendidikan. Kebijakan jarak sosial dan fisik telah memaksa proses pembelajaran di sekolah terhenti. Belajar di rumah dengan moda pembelajaran jarak jauh dan daring menjadi satu-satunya pilihan untuk memecahkan masalah tersebut. Artikel ini berupaya menjawab dua hal. Pertama, apa esensi ruang belajar dalam konteks e-learning ditinjau dari sudut pandang ruang dan waktu? Kedua, apa implikasinya dalam pembelajaran di era Covid-19 dan tatanan baru? Peneliti menggunakan metode kajian pustaka untuk menjawab pertanyaan tersebut. Berdasarkan hasil kajian pustaka, diperoleh empat klasifikasi ruang belajar baru dan implikasi terhadap pembelajaran di era Covid-19 dan tatanan baru.